Long-term effects of a progressive and specific balance-training programme with multi-task exercises for older adults with osteoporosis: a randomized controlled study. (November 2016) - Halvarsson, Alexandra; Oddsson, Lars; Franzén, Erika; Ståhle, Agneta
Objective: To evaluate long-term effects of balance-training on concerns about falling, gait, balance performance, and physical function in older adults with osteoporosis and increased risk of falling. Design: Randomized controlled trial, including three groups (training, training+physical activity, and control group), with follow-ups at three, nine, and 15 months. Short-term, three-month follow-up, benefits for those who fulfilled the first follow-up ( n  = 69) have previously been reported. Setting: Stockholm, Sweden. Participants: A total of 96 elderly, age 66–87, with verified osteoporosis. Interventions: Balance-training programme including dual- and multitasks, with or without supplementary physical activity, three times/week over 12 weeks. Measurements: Concerns about falling Falls Efficacy Scale -International (FES-I), walking at preferred speed with and without a cognitive dual-task and at fast speed, balance tests (one-leg stance and modified figure-of-eight), and physical function Late-Life Function and Disability Instrument (LLFDI). Results: Participants in the training group maintained positive effects throughout the study period for concerns about falling (baseline vs. 15 months, median 27.5 vs. 23 points, p  < 0.001) and walking performance (baseline vs. 15 months, p  ⩽ 0.05 with an improvement of 0.9–1.4 m/s). The Training+physical activity group declined to baseline values at the nine-month follow-up, and were even lower at the 15-month follow-up for concerns about falling (median 26 vs. 26 points), walking performance (changes of −0.02 to 0.04 m/s), and physical function (mean 44.0 vs. 42.9 points). The control group remained unchanged throughout the study period. Conclusions: This balance-training programme reduced concerns about falling, and also improved gait in older adults with osteoporosis and increased risk of falling in a long-term perspective – important issues for fall prevention.